“HIS ANTICIPATION OF A CAREFULLY PLANNED LIFE AFTER THE CATASTROPHE PROVES HAVING A PERSPECTIVE” – TOPONYMS IN GÜNTER GRASS’S NOVEL DIE RÄTTIN AS A TRANSLATION AND LITERARY THEORY PROBLEM - Kubaszczyk, Joanna (Porównania, 2019)
Grass’s novel Die Rättin is a multi-faceted piece of work reflecting on the past, present and future, combining realism with fairy tales and myth. The anti-utopian project of the future plays a special role in the novel. In the article, the author analyzes the functions and translations of toponyms in Grass’s novel and its Polish translation by Błaut examining how far the project of the future is identical in the original and translation and whether the translation strategy of toponyms selected by the translator is a correct strategy or whether it leads to the loss of multiple references and it destroys the author’s complicated creation of a city with a double identity.